Speech therapy in oropharyngeal dysphagia in patients with Multiple Sclerosis (Research, Society and Development, 2025)
Multiple Sclerosis (MS) is an autoimmune neurological disease that affects the central nervous system, causing a variety of symptoms, including oropharyngeal dysphagia. In turn, dysphagia refers to difficulty swallowing, which can lead to aspiration, malnutrition, dehydration and lung problems. The objectives of this study are to deepen the impacts of oropharyngeal dysphagia in patients with MS, as well as speech therapy intervention. Methodology: The study was completed between August and November 2024. A survey of articles was carried out in 4 databases, namely: Virtual Health Library (BVS), Public Medicine Library (PubMed), Capes Periodicals and Scientific Electronic Library Online (SciELO), then the descriptors were established in Portuguese and English. The inclusion and exclusion criteria that guided the search were defined. Initially, 249 articles were identified in the databases. After the bibliographic survey and application of the exclusion criteria, 16 articles were selected. Results: Of the 16 articles included in this review, multiple sclerosis and speech-language disorders were unanimously addressed in the articles. Ten articles presented speech-language findings on swallowing biomechanics; 5 reported protocols used; and 1 reported on the strategy that would facilitate quality of life. Conclusion: The research deepened knowledge about speech-language therapy in patients with MS and dysphagia, through an integrative review of the literature. Oropharyngeal dysphagia in patients with MS proved to be a multifaceted condition, with significant implications for quality of life. The present research demonstrates the importance of speech-language therapy, highlighting the need for early and individualized interventions.